KONTRIBUSI CARA BELAJAR TERHADAP HASIL BELAJAR PENGOLAHAN DAN PENYAJIAN MAKANAN KONTINENTAL SISWA PROGRAM KEAHLIAN JASA BOGA SMKN 2 BUKITTINGGI - Zaimel, Yossy; Yulastri, Asmar; Faridah, Anni (Journal of Home Economics and Tourism, 2017)
This study aims to analyze the contribution of learning to the learning outcomes Continental Food Processing and Presentation of student membership food service program SMKN 2 Bukittinggi. This type of research is quantitative descriptive by using the correlation method. The subjects of this research were students of class XI SMKN 2 Bukittinggi, amounted to 70 people. Collecting data through direct observation and measurement using a questionnaire with Likert Scale. Hypothesis testing using correlation coefficient analysis. Based on the results of research shows that learning PPMK of food service student SMKN 2 Bukittinggi in both categories with a percentage of 70% and the learning outcomes in categories with a percentage 54.3%, with a correlation coefficient of 0.27. the hypothesis proposed (Ha) recieved, which reads some positive contribution and significant between learning styles to student learning outcomes Continental Food Processing and Presentation of SMKN 2 Bukittinggi.Kata Kunci: Learning, Learning Outcomes, Continental Food Processing and Presentation